Self-Expandable Stents in the Gastrointestinal Tract - Kozarek, Richard; Baron, Todd; Song, Ho-Young (Springer New York : Imprint: Springer, 2013)
Self-expandable stents were initially placed for the treatment of cardiovascular diseases but now play an integral role in the relief of benign and malignant obstruction of the gastrointestinal tract and biliary system.  Self-Expandable Stents in the Gastrointestinal Tract will familiarize the reader with the indications, techniques, and outcome following placement of expandable metal stents within the gastrointestinal tract. The volume covers all aspects of expandable stents including their composition, tissue responses, and placement techniques. In addition, placement using endoscopic and radiologic techniques is discussed. Unique illustrations allow the reader to gain knowledge that will improve their ability to care for their patients. The volume will serve as a comprehensive reference for all aspects of expandable stents. Self-Expandable Stents in the Gastrointestinal Tract will be extremely useful for physicians in the field of gastroenterology, endoscopy, and radiology, as well as gastrointestinal and thoracic surgeons whether they are in training or practice.  .